Analysis of the Incidence of Klebsiella Pneumoniae in Respiratory Infections - Shaydullaevna, Fotima Mamatmusaeva; Alievich, Saidshokh Jumaev; Zafar o’gʻli, Abbos Raimqulov (American Journal of Bioscience and Clinical Integrity, 2025)
Although occurrences of hypervirulent Klebsiella pneumoniae (hvKp) strains are becoming more frequent, they are still thought to be rather uncommon in the US. Between 2020 and 2022, we prospectively and serially gathered clinical isolates of K. pneumoniae found in respiratory specimens at a Western Pennsylvania health system. The string test for a hypermucoid phenotype and multiplex PCR were used to identify isolates expressing the cardinal virulence genes rmpA, rmpA2, iutA, and iro in a total of 273 K. pneumoniae isolates from 216 distinct patients. Thirteen (4.8%) of the 273 isolates, including 11 nonduplicate K. pneumoniae isolates, tested positive by the string test. Two of these isolates (0.7%) tested positive by PCR for the virulence genes rmpA, rmpA2, iutA, and iro. The second two probable hvKp strains were obtained from community-associated infections in people without known travel histories and belonged to sequence types ST23-K1 and ST86-SLV-K2. They carried pLVPK-like plasmids. Human serum did not kill the probable hvKp strains or the two other bacteria that tested positive in the string test. animals infected by oropharyngeal aspiration developed substantial pneumonia due to the hvKp strains; animals infected with the KL1 (ST23) strain had a significantly larger bacterial burden in their lungs and a significantly higher weight loss than mice infected with the KL2 (ST86-SLV) strain. Additionally, we found that mice infected with the KL1 strain had a lower survival rate than those infected with the KL2 strain. These results contribute to the increasing amount of data indicating that hvKp strains that were previously thought to be endemic to Asia may now be spreading throughout North America.